2022
DOI: 10.3390/molecules27051582
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Salvia miltiorrhiza Extract and Its Active Components on Cervical Intraepithelial Neoplastic Cells

Abstract: The effective treatment of cervical intraepithelial neoplasia (CIN) can prevent cervical cancer. Salvia miltiorrhiza is a medicinal and health-promoting plant. To identify a potential treatment for CIN, the effect of S. miltiorrhiza extract and its active components on immortalized cervical epithelial cells was studied in vitro. The H8 cell was used as a CIN model. We found that S. miltiorrhiza extract effectively inhibited H8 cells through the CCK8 method. An HPLC–MS analysis revealed that S. miltiorrhiza ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…In addition, salvianolic acid A can inhibit thymidine and uridine transport of ascites cancer cells, enhance the cytotoxicity of 5-fluorouracil, mitomycin C and methotrexate on KB cells and liver cancer BEL-7402 cells, and enhance the anti-tumor effect of chemotherapy drugs [17]. In terms of gynecological tumors, Leng et al [18] showed that salvianolic acid A combined with sophordine oxide could cooperatively regulate the cell cycle of cervical epithelial immortalized cells (H8), inhibit the expression of Bcl-2 protein, elevate the expression of Bax and Cleaved Caspase-3 protein, block H8 cells in the G2/M stage, and impede the proliferation of H8 cells. Promote their apoptosis.…”
Section: Effective Components Of S Miltiorrhiza and Their Antitumor E...mentioning
confidence: 99%
“…In addition, salvianolic acid A can inhibit thymidine and uridine transport of ascites cancer cells, enhance the cytotoxicity of 5-fluorouracil, mitomycin C and methotrexate on KB cells and liver cancer BEL-7402 cells, and enhance the anti-tumor effect of chemotherapy drugs [17]. In terms of gynecological tumors, Leng et al [18] showed that salvianolic acid A combined with sophordine oxide could cooperatively regulate the cell cycle of cervical epithelial immortalized cells (H8), inhibit the expression of Bcl-2 protein, elevate the expression of Bax and Cleaved Caspase-3 protein, block H8 cells in the G2/M stage, and impede the proliferation of H8 cells. Promote their apoptosis.…”
Section: Effective Components Of S Miltiorrhiza and Their Antitumor E...mentioning
confidence: 99%
“…e preparation and isolation of the lignans from M. scabra were employed as previous studies reported [20][21][22]. About 15 kg of aerial parts of the plant was extracted with 30 L of 95% ethanol 2 times for 24 h by using the heating reflux method.…”
Section: Preparation Of Herbal Extracts and Lignan Isolationmentioning
confidence: 99%
“…With more and more chemical and pharmacological researches on Salvia miltiorrhiza, researchers have found that Salvia miltiorrhiza exhibit diverse biological functions, such as anti-tumor, anti-oxidative stress, antithrombosis, anti-inflammatory, anti-liver fibrosis and antidiabetes activities (Guo et al, 2014;Zhou et al, 2014;Jiang et al, 2019;Petitjean et al, 2022). These effects are attributed to its wide range of bioactive ingredients, including tanshinone I, tanshinone IIA, tanshinone, procatechualdehyde, polysaccharide, salvianolic acids and other chemical substances (Jia et al, 2019;Kapalavavi et al, 2021;Leng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%